Pengaruh Waktu Detensi Terhadap Efisiensi Penyisihan COD Limbah Cair Pulp Dan Kertas dengan Reaktor Kontak Stabilisasi - Muria, Sri Rezeki; Tasbieh, Hayatrie; Ahmad, Adrianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Every year the production of pulp and paper continued to increase. This resulted in the wastewater produced in large quantities. Characteristics of Chemical Oxygen Demand (COD) in the pulp and paper effluent is 3500 mg/L. COD is one of the important parameters in determining the quality of wastewater and measurement of water pollution by organic substances. High value of COD in waste water indicates that the degree ofcontamination at a higher too. Therefore, the pulp and paper wastewater treatment is necessary before it is discharged into waters. COD handling of pulp and paper wastewater can be aerobically by using the stabilization contact reactor. The aim of this study is to set aside the content of COD and determine the effect of detention time on COD removal efficiency and optimum pH of pulp and paper effluent. The results showed that the CODremoval by varying the detention time for 1 hour, 2 hours, 3 hours and 4 hours, the highest COD removal efficiency obtained at 4 hours in the amount of 87.14 % with pH of 8.0. Thissuggests that the stabilization contact reactor is stabilized in removing wastewater COD content of the pulp and paper.Keyword: Aerobic, Provision for the content of COD, Pulp and paper wastewater, Stabilization contact reactor.